FINTECH ERA AND GOVERNMENT REGULATION - Erie Hotman H Tobing; Adrian Adrian (Jurnal Manajemen dan Bisnis Jayakarta, 2020)
The growth of Fintech Lending according to OJK data as of November 2019 accumulated loans amounting to Rp 74.54 trillion, an increase of 228.88% ytd, with 164 registered / licensed operators. Fintech lending illegal that has been acted upon by the Investment Alert Task Force from 2018 to November 2019 as many as 1,898 entities. The latest findings at the end of November 2019 were 125 illegal fintech lending that were not registered in the OJK had been reduced from Google Play. Data from the Indonesian Joint Funding Fintech Association (AFPI) with 164 organizers as of mid-December 2019 noted that there were 25 AFPI members who obtained business licenses from the FSA, while 139 other AFPI members were registered with the FSA through the licensing process. Ease of access and approval process that is instant compared to approval compared to the banks caused an increase in borrower growth. But behind that, of course there are also many irregularities that occur in illegal organizers. The effects of fintech's growth have an impact on the growth of conventional banking applications, which are reaching the digital age as well